Relevance of the C-5 Position to Schweinfurthin Induced Cytotoxicity - Topczewski, Joseph J. (2011)
The schweinfurthins are an intriguing group of anti-proliferative agents that display low nanomolar activities against several cell types, including the human-derived glioblastoma cell line SF-295, but have little impact on other cell lines even at micromolar concentrations. This activity has inspired the synthesis of seven of the natural schweinfurthins, all with the correct absolute stereochemistry, and a variety of analogues designed to probe different facets of the pharmacophore. Reported herein is the synthesis of several new schweinfurthin analogues varied at the C-5 position along with data on their biological activity in the NCI 60 cell-line assay.